Karakteristik Kimiawi Bakso Ikan Patin (Pangasius pangasius) Dengan Penambahan Tepung Jamur Tiram Putih (Pleurotus ostreatus): Karakteristik Kimiawi Bakso Ikan Patin (Pangasius pangasius) Dengan Penambahan Tepung Jamur Tiram Putih (Pleurotus ostreatus) - Wibowo, Tri Adi (JURNAL PENGOLAHAN PERIKANAN TROPIS, 2024)
Pangasius catfish is a fish that is consumed quite a lot in Indonesia because the meat is quite tasty, delicious and tasty. Meatballs are one of the most popular processed meat-based food products. However, the meatball products that we encounter are not sufficient for the consumption of dietary fiber. Oyster mushroom is a type of mushroom that contains high fiber, which is 11.5%. The high production of catfish farming which is not matched by product diversification that is attractive to people in East Lampung is the background of this research. This study aims to optimize the results of catfish cultivation products with product diversification in the form of pangas catfish meatballs with the addition of white oyster mushroom flour so that they can provide additional nutritional value and increase public interest in consuming fishery products. Nutritional content was studied by proximate analysis to determine the levels of protein, carbohydrates, ash content, water content, crude fiber and fat content contained in pangas catfish meatballs with the addition of oyster mushroom flour Processing of pangas catfish meatballs with the addition of 5% of oyster mushroom flour White flour generally provides additional nutrients moisture content 71,5498 %, ash content 1,7157 %, fat content 1,1186 %, protein content 6,2199, crude fiber content 6,5916 % and carbohydrate content 19,3960 % slightly higher than meatballs without the addition of white mushroom flour. The nutritional content of meatballs with the addition of white mushroom flour meets and approaches the nutritional standards of the 2017 National Standardization Agency (BSN), namely ash content, fat content and protein content, except for water content. Furthermore, carbohydrate content and crude fiber content were not listed, so all treatments were considered as added value from catfish meatballs with the addition of white oyster mushroom flour